DETERMINAN DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fauziah, Fenty; Martihen Supriyadi; Fitri Darmayani Manoy (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2023)
This research has the aim of knowing and analyzing the effect of the Net Profit Margin and Tax Rate partially and simultaneously on the Dividend Payout Ratio in manufacturing companies listed on the Indonesia Stock Exchange.Secondary data collection is the method utilized to gather the data, and it can be accessible through the official websites of the Indonesia Stock Exchange and official websites of the company that was chosen as the research sample. With a sample selection technique utilizing purposive sampling, the population considered is all manufacturing enterprises registered on the Indonesia Stock Exchange. Panel data analysis is the method of data analysis used using the statistical software Eviews. Partially, Net Profit Margin has a significant negative effect on the Dividend Payout Ratio and the Tax Rate has a significant negative effect on the Dividend Payout Ratio. Simultaneously Net Profit Margin and Tax Rate have a significant effect on the Dividend Payout Ratio. The research conducted can be useful for researchers and readers to add insight and knowledge. Likewise, investors who want to invest in the manufacturing sector can consider the Net Profit Margin and Tax Rate factors because they have a significant influence on the Dividend Payout ratio.